Evaluation of Islamic Religious Education Curriculum in Indonesia: Case Study at Elementary and Secondary School Levels - Fiqi Fahlevi; Juliani; Muhammad Raihan Nasution; Muhammad Ikhsan Prabudi; Ihsan Maulana (Journal of Contemporary Islamic Primary Education, 2023)
There are many problems and solutions for the development and implementation of the PAI curriculum in schools and madrasahs. This research aims to identify the problems and solutions of the school and madrasah curriculum. This research falls into the category of library research. The evaluation results indicate that it is important for all stakeholders in public schools to pay more attention to students' attitudes in order to create the next generation that is socially and spiritually sensitive. Second, the issues that arise in the development of the Madrasah PAI curriculum should make local governments better understand that Islamic religious education is the responsibility of local governments.